An Innovative Low-Cost Equipment for Electro-Concentration of Microalgal Biomass (2020)
Microalgal harvesting is one of the most challenging processes in the development of algal research and development. Several methods, such as centrifugation, flocculation and filtration, are available at the laboratory scale. However, the requirement for expensive pieces of equipment and the possibility of biomass contamination are recurring gaps that hinder the development of microalgae R&D (research and development) in different parts of the world. Recently, electroflotation has been proved to be a suitable method for the harvesting of different species of microalgae and cyanobacteria. To this day, there are no companies that sell laboratory-scale electroflotation equipment; this is mainly due to the gap in the knowledge of which factors (time, mixing rate, number of electrodes and others) will affect the efficiency of concentration without reducing the biomass quality. This paper aims to build an innovative, low-cost electroflotation system for under 300 USD (United States dollar) with cheap and resistant materials. To achieve our goal, we tested the interaction of three variables (time, mixing rate and amount of electrodes). Results showed that an efficiency closer to 100% could be achieved in under 20 min using > 10 electrodes and 150 rpm (round per minute). We hope this innovative approach can be used by different researchers to improve our knowledge of the concentration and harvesting of algae and cyanobacteria.